Early Regulation of Profibrotic Genes in Primary Human Cardiac Myocytes by Trypanosoma cruzi. - Aniekanabassi N Udoko; Candice A Johnson; Andrey Dykan; Girish Rachakonda; Fernando Villalta; Sammed N Mandape; Maria F Lima; Siddharth Pratap; Pius N Nde (Public Library of Science (PLoS), 2016)
The molecular mechanisms of Trypanosoma cruzi induced cardiac fibrosis remains to be elucidated. Primary human cardiomyoctes (PHCM) exposed to invasive T. cruzi trypomastigotes were used for transcriptome profiling and downstream bioinformatic analysis to determine fibrotic-associated genes regulated early during infection process (0 to 120 minutes). The identification of early molecular host responses to T. cruzi infection can be exploited to delineate important molecular signatures that can be used for the classification of Chagasic patients at risk of developing heart disease. Our results show distinct gene network architecture with multiple gene networks modulated by the parasite with an incline towards progression to a fibrogenic phenotype. Early during infection, T. cruzi significantly upregulated transcription factors including activator protein 1 (AP1) transcription factor network components (including FOSB, FOS and JUNB), early growth response proteins 1 and 3 (EGR1, EGR3), and cytokines/chemokines (IL5, IL6, IL13, CCL11), which have all been implicated in the onset of fibrosis. The changes in our selected genes of interest did not all start at the same time point. The transcriptome microarray data, validated by quantitative Real-Time PCR, was also confirmed by immunoblotting and customized Enzyme Linked Immunosorbent Assays (ELISA) array showing significant increases in the protein expression levels of fibrogenic EGR1, SNAI1 and IL 6. Furthermore, phosphorylated SMAD2/3 which induces a fibrogenic phenotype is also upregulated accompanied by an increased nuclear translocation of JunB. Pathway analysis of the validated genes and phospho-proteins regulated by the parasite provides the very early fibrotic interactome operating when T. cruzi comes in contact with PHCM. The interactome architecture shows that the parasite induces both TGF-β dependent and independent fibrotic pathways, providing an early molecular foundation for Chagasic cardiomyopathy. Examining the very early molecular events of T. cruzi cellular infection may provide disease biomarkers which will aid clinicians in patient assessment and identification of patient subpopulation at risk of developing Chagasic cardiomyopathy.